2023
DOI: 10.1021/acs.joc.3c00284
|View full text |Cite
|
Sign up to set email alerts
|

Access to 3-Aminomethylated Maleimides via a Phosphine-Catalyzed Aza-Morita–Baylis–Hillman Type Coupling

Abstract: A designed method for the preparation of 3-aminomethylated maleimides via Morita−Baylis−Hillman (MBH) reaction was developed. This phosphine-catalyzed coupling adopted maleimides and 1,3,5-triazinanes as the substrate, giving a series of 3-aminomethylated maleimide derivatives with a double bond retained on the maleimide ring in 41−90% yield. Acylation, isomerization, and Michael addition of the obtained products demonstrated the synthetic application of the present protocol. The results of control experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…An efficient strategy for the synthesis of 3-aminomethylated maleimides through the MBH reaction has been established. 44 The MBH reaction between maleimides and 1,3,5-triazinanes was achieved under optimized conditions (20 mol% PPh 3 as the catalyst, 20 mol% PhCO 2 H as the promoter in DCE at 70 °C for 15 min) ( Scheme 28 ). In this method, N -phenylmaleimide derivatives with electron-donating and electron-withdrawing substituents participated to create the desired product in satisfactory yields.…”
Section: The Morita–baylis–hillman Reaction Using Phosphines As Catal...mentioning
confidence: 99%
“…An efficient strategy for the synthesis of 3-aminomethylated maleimides through the MBH reaction has been established. 44 The MBH reaction between maleimides and 1,3,5-triazinanes was achieved under optimized conditions (20 mol% PPh 3 as the catalyst, 20 mol% PhCO 2 H as the promoter in DCE at 70 °C for 15 min) ( Scheme 28 ). In this method, N -phenylmaleimide derivatives with electron-donating and electron-withdrawing substituents participated to create the desired product in satisfactory yields.…”
Section: The Morita–baylis–hillman Reaction Using Phosphines As Catal...mentioning
confidence: 99%
“…As part of our long-term interest in developing sulfur-containing compounds, we herein report a glyoxylic acid monohydrate-promoted hydrosulfonylation of 1,4-diketones by using sodium sulfite, which is a safe and green sulfone source. This protocol would provide an efficient and quick access to form the C–SO 2 bond (Scheme , this work), and it can also be applied on the hydrosulfonylation of maleimide blocks, which are widely found in natural products and drug molecules …”
Section: Introductionmentioning
confidence: 99%
“…Besides the metal-catalyzed oxidative amination, we found that 3-aminomaleimde could be easily obtained after simply mixing 1g , anisidine, and 3 , which proved the indispensable role of sulfur for promoting the double bond construction ( eq c ). Next, 3-(aminomethyl)­maleimide was prepared and treated with elemental sulfur and formaldehyde solution. 4g could not be detected in the reaction mixture, which excluded the possibility of 6g serving as a potential intermediate ( eq d ).…”
mentioning
confidence: 99%